Impact of diurnal temperature and salinity on chlorophyll fluorescence in Strawberry - Francisco-Francisco, Nazario; Benavides-Mendoza, Adalberto (Revista Mexicana de Ciencias Agrícolas, 2018)
This study was conducted to investigate the behavior of the chlorophyll fluorescence of plants of strawberry (Fragaria x ananassa) with the daytime temperature salinity and low emissions. For this, strawberry plants were established in pots of black polyethylene with a capacity of 5 L containing peat moss as substrate. Salinity treatments were induced by the application of CaCl2 at 0 and 12 mM, which was added to a nutrient solution Steiner. The control and the treated plants grown in a greenhouse ventilated with exhaust fans and were irrigated every two days. The investigation of the impact of diurnal temperature on chlorophyll f luorescence recording was made greenhouse temperature every hour between 8:00 am to 5:00 pm. Measurements of the f luorescence parameters were performed on days 0, 14, 28, and 42 after initiation of salinity treatments.Treatmentof12mMofCaCl2 reducedthemaximum quantum efficiency (Fv / Fm) and effective (EPS2) but did not increase the decay non-photochemical (NPQ) is interpreted as a response to the PSII minimal involvement.As to the temperature decrease in the plants showed the Fv/Fm and EPS2 air temperatures exceeding 28 °C. The maximum photochemical ef f iciency was observed with temperatures below 19 °C.